Protocol for the implementation evaluation of an integrated paediatric and primary care model: Strengthening Care for Children (SC4C) - Yvonne Zurynski; Susan Woolfenden; Peter D Hibbert; Harriet Hiscock; Raghu Lingam; Karen Wheeler; Michael Hodgins; Jade Burley; Rachel Pelly; Jane Le; Sonia Khano; Tammy Meyers Morris; et al. (BMJ Open)
Introduction Implementation evaluations provide insight into how interventions are delivered across varying contexts and why interventions work in some contexts and not in others. This manuscript outlines a detailed protocol of an implementation evaluation embedded in a stepped-wedge cluster randomised controlled trial of a model of care, Strengthening Care for Children (SC4C), that integrates paediatric care in general practice. The purpose of this manuscript is to describe the pragmatic methods that will be used to capture implementation evaluation process and outcome data within this trial.Methods and analysis Our implementation evaluation will use a mixed methods design, with data collected in the intervention arm of the SC4C trial guided by a logic model developed using the Consolidated Framework for Implementation Research (CFIR) and Proctor and colleague’s taxonomy of implementation outcomes. Data collection will be via questionnaires and semistructured interviews with general practitioners, paediatricians, general practice administrative staff and children and families. Each of the 21 general practices recruited into the study will be described in terms of staffing, patient throughput and location, in addition to the nuanced inner and outer contexts, use of the intervention and its acceptability. We will quantify implementation effectiveness in each general practice clinic using the CFIR validated scoring system. Importantly, we have embedded data collection post intervention to enable assessment of the sustainable adoption of the intervention. An inductive approach to the analysis of qualitative data will identify additional emerging themes that may not be covered by the formal frameworks underpinning our analysis.Ethics and dissemination Ethical approval was granted by the Royal Children’s Hospital Ethics Committee in August 2020 (HREC: 65955). Results will be submitted for publication in peer-reviewed journals and presented at relevant conferences.Trial registration number Australia New Zealand Clinical Trials Registry 12620001299998 on 1 December 2020.